Development of Tourism Villages Based on Local Culture to Increase Community Income at Dokan, Karo North Sumatera - Revida, Erika; Badaruddin (Talenta Publisher, 2022)
The purpose of the community service of the professors serving scheme in 2021 is to increase the understanding, knowledge and commitment of the community in the Dokan tourist village, Karo, North Sumatra to the importance of developing tourism village based on local culture to increase people's income. This community service of the serving professor is carried out by lecture and question and answer methods, namely socialization by communication, information, and education (KIE) about the need to develop a tourism village based on local culture, namely Karo culture, so that it is attractive to tourists, both local and foreign tourists. The results of community service activities, professors serving scheme in 2021 which were carried out in the tourist village of Dokan, Karo, North Sumatra went well and smoothly without significant obstacles even though in the midst of the Covid-19 pandemic by implementing strict health protocols and the number of participants was limited to 25 people only. Participants were very enthusiastic about asking questions and providing information and statements about how to develop a tourism village based on local culture, namely the Karo traditional house. The community service team of professors serving scheme Universitas Sumatera Utara provides solutions so that mutual cooperation is carried out at least every Saturday to maintain the Karo Traditional house in the tourist village of Dokan, Karo, North Sumatra and proposes a proposal for the maintenance of the Karo traditional house to the local government and central government and related interest groups.